Juventudes, educação e desigualdades sociais: o papel da escola no Projeto de Vida dos jovens - Farias, Francisca Bruna Pereira (2023)
The present work comes up with a synthesis of the research carried out during the Master's Degree in Psychology and Public Policies, which aimed to investigate the role of the school in the life project of high school students. Specifically, the work sought to build a study that went beyond research itself, but a training moment, not only for the researcher, but also for the participants and, thus, analyze the existing relationships between youth, education, life project and social inequality. Seeking to understand the vision that young people have of the school, the role they attribute to it in the construction and realization of their life projects, and how their social realities impact on these projects. In addition, the work proposed to elaborate together with the research participants a Guiding Curriculum Script, with the systematization of themes that the students consider important to be approached for the development of the curricular component life project. The study consisted of a research-training with a qualitative approach. 65 students participated in the present research, regularly enrolled in the School of Secondary Education in Full Time (EEMTI) Ayres de Sousa, located in the district of Jaibaras-Sobral, linked to the 6th Regional Coordination for the Development of Education-Sobral. The first part of the data collection took place through a survey of the socioeconomic profile of the students, which took place through an Online Form completed by the students who agreed to participate in the research, by signing the Term of Free and Informed Consent - TCLE. The second part of data collection took place from the execution of narrative and autobiographical workshops, which took place at school through face-to-face meetings. Five workshops were carried out during the classes of the Core of Work, Practices and Social Research (NTPPS) discipline and also had the participation of the teacher. Data analysis was carried out through the content analysis of the materials produced during the workshops and through the data generated in the forms, which were organized into categories of analysis and discussed in this dissertation. Knowing the importance of developing research that produces tools that impact on improvements in the realities researched, the study enabled the construction of some technical products, including the RCO, the systematization of narrative and autobiographical workshops, as well as academic products, such as scientific articles.